PENINGKATAN DAYA TARIK WISATA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA WISATA CIHIDEUNG UDIK BOGOR - Ardiansyah, Imam; Krisnadi, Antonius Rizki; Dewantara, Yudhiet Fajar; Iskandar, Hari; Natalia, Dessy; Facrureza, Dewanta; Rosanto, Stephanie; Vishnuvardhana, Vishnuvardhana; Hema, Lamtiar (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The implementation of the Community Service Program by the Hospitality and Tourism Study Program of Bunda Mulia University, designed with the main goal of expanding knowledge and enhancing the skills of participants, especially in understanding the potential of Cihideung Udik Village. This activity is also aimed at facilitating the establishment of cooperation and partnerships between Bunda Mulia University and the managers of Cihideung Udik Village, as a realization of the development of social competencies for lecturers. The conclusion highlights the role of Community Service as a platform where lecturers can share knowledge with the community, focusing on improving the quality of life, especially for participants from Cihideung Udik Village. Community Service is also considered a space that provides valuable experiences and guidance for participants, preparing them with practical knowledge to establish their own businesses and manage the potential of village tourism with high expertise. This conclusion reflects a commitment to comprehensive community development and the empowerment of village potential through participatory and educational approaches.edukatif